How to scale Management Advice for Family Farms in Africa. Issue 4 (2nd October 2018) - Faure, Guy; Toillier, Aurélie; Moumouni, Ismail
ABSTRACT: In Africa, farm advisory services are still dominated by the model of technology transfer. During the last two decades a new approach, based on adult learning methods, has been successfully introduced (Management Advice for Family Farms, or MAAF). The current challenge is to improve access to and the institutional and financial sustainability of MAFF. To this end, we conducted a participatory evaluation of existing MAFF services using four criteria: governance, funding modalities, capacity of advisors and adaptation of the method. We found that the main constraint to scaling MAFF is institutional. Giving producers' organisations a greater say in governance would facilitate more appropriate advice, reduce costs and strengthen the services' sustainability beyond project-level investments.